Application of the 3D digital ostectomy template (DOT) in mandibular angle ostectomy (MAO). Issue 10 (October 2018) - Zhang, Chao; Ma, Merry W.; Xu, Jia-Jie; Lu, Jian-Jian; Xie, Fang; Yang, Li-Ya; Li, Shu-Yuan; Wu, Huan-Huan; Sun, Heng; Yang, Biao; Teng, Li
Abstract: Background: Mandibular angle ostectomy (MAO) is a standard approach in reconstruction of facial contour that is commonly used in East Asian patients with prominent mandibular angles (PMA). MAO is commonly performed via an intraoral approach to reduce scar visibility and risk of facial nerve injury. Since this intraoral approach for MAO has limited visual guidance during the procedure, plastic surgeons often perform the operation based on personal clinical experience. Therefore, we designed a 3D digital ostectomy template (DOT) for guidance during surgery to improve the accuracy and safety of MAO. Methods: 10 female patients (average age 25.3 years) with PMA were enrolled in this study from August 2014 to October 2015. The DOTs were designed and printed preoperatively and utilized in the operation to guide the osteotomy. The excised mandibular angle bone and the DOTs were measured respective to each other. The data were analyzed to verify the feasibility and safety of the DOT. Results: All of the patients were satisfied with the surgical results, and no complications such as fracture, hemorrhage and infection occurred. The distance from gonion (Go) along inferior margin of mandible forward to the distal end of the excised bone is "a". The distance from Go along posterior margin of ramus upward to the distal end of the excised bone is "b". The widest distance from Go to the ostectomy line is denoted by "c". Similarly, the corresponding distance in the DOT is denoted by "a'", "b'", "c'". The statistical results showed that left a vs a', b vs b', c vs c' was 63.27 ± 6.39 mm vs 62.97 ± 6.30 mm (p > 0.05), 23.98 ± 2.25 mm vs 21.83 ± 2.27 mm (p < 0.05), 13.58 ± 2.24 mm vs 13.37 ± 2.14 mm (p > 0.05), respectively. The right a vs a', b vs b', c vs c' was 62.92 ± 5.00 mm vs 62.72 ± 4.99 mm (p > 0.05), 24.03 ± 1.88 mm vs 21.80 ± 1.91 mm (p < 0.05), 13.36 ± 1.70 mm vs 13.22 ± 1.72 mm (p > 0.05), respectively. The results indicate a significant difference between b and b' both on the right and left sides. Conclusion: Through the application of DOT in MAO, the accuracy and safety of the operation were improved significantly. Unfortunately, the osteotomy could not be guided well in the posterior rim of the ramus. Further improvements in the surgical template are needed for application in PMA associated with oversized chin deformity or in PMA associated with large mandibular angle and severe involution.